Local Wisdom Represented by Words in Nonik Performance Ritual in Lembu Village, Semarang Regency - Retno M, Laura Andri; Chandra, Oktiva Herry (2024, 2024)
Noknik art performance is a combination of theater and movement art that has developed in Semarang Regency. The uniqueness of Noknik art can be seen in the musical accompaniment of tambourines and poetry using a combination of Kawi and Arabic languages. This lyric of the art performance ritual is full of advice and guidance for life. This research aims to reveal lyrics containing local wisdom to share with audiences during the performance. The method used in this research is the descriptive qualitative method through qualitative research. The steps in qualitative research are (1) collecting data through participant observation, in-depth interviews with Noknik arts groups, documentation, and focus group discussions; (2) data reduction and classification; (3) data analysis; and (4) staging and concluding. The result shows that the lyrics of the art performance ritual are full of local wisdom. This local wisdom can be seen from the words used during the ritual. Each component in each step of the ritual depicts these people in understanding the relation between the villagers and their ancestors, villagers and nature, and villagers and God. The words of each ritual component also symbolize the way people think of their world. Nonik art performance allows villagers to strengthen social bonds, intensive conversation, and experience sharing among members of similar cultural backgrounds and communities.
Keywords: art performance, local wisdom, ritual, ancestor, villagers, and nature